Open science: Development, challenges and practice in the global context. Issue 1 (1st February 2019) - Chen, Hsin‐liang; Liu, Ying‐Hsang; Pei, Lei; Peters, Isabella; Smith, Ina
ABSTRACT: Open science (OS) is a global issue concerning how researchers work, collaborate, interact, share resources, and disseminate results in the digital age. This panel assembles researchers from various continents to discover their experiences and to address some of the following issues: What is the state of OS policies in the region? Does the region have any international, national, or regional OS collaborations and/or agreements? Does the region have any international, national or regional OS infrastructure and/or systems? Are international, national or regional OS standards being adapted in the region? What is the utilization level of the OS infrastructure and/or systems in the region? Is the region experiencing any progress, barriers and/or challenges in implementing the OS initiatives?